Reviewed Reasoning Based on the Monograph by Tatyana Alekseeva “The Head of the Spanish State: the History of Constitutionalization” - K. V. Aranovsky (Теоретическая и прикладная юриспруденция)
In the article, the author examines the monograph by Tatyana Alekseeva. “The Spanish Head of State: A History of Constitutionalization”. The author notes the relevance of the study by Tatyana Alekseeva Institute of the Head of State, as relevant in modern conditions. The author notes that this historical and legal study has every reason to claim recognition in constitutional and legal comparative studies, as well as in the science of constitutional law in a broad theoretical sense. The author analyzes the role of the monarchy as an institution, on the one hand, exerting a restraining effect on the state of society, and on the other, serving as the basis, including for a democratic social order, based on the force of law. Research by Tatyana Alekseeva proves that free and careless treatment of state and legal institutions is costly for people, estates and nations.